Smart Contracts: A South African Perspective. A legal analysis of the possibilities and challenges posed to the recognition and enforcement of smart contracts under the South African law of contract - Esau, Oriana (Department of Commercial Law, 2024)
The advent of electronic commerce has allowed for various transactions to be moved online. Coupled with the dawn of the Fourth Industrial Revolution and the technological progress which precipitated it, traditional modes of commercial transactions have been disrupted by the options available to actors within the marketplace when executing contracts of a commercial nature